Demystifying and puncturing the inflated delay in smartphone-based WiFi network measurement - LI, Weichao (Institutional Knowledge at Singapore Management University, 2016)
Using network measurement apps has become a very effective approach to crowdsourcing WiFi network performance data. However, these apps usually measure the user-level performancemetrics instead of the network-level performance which is important for diagnosing performance problems. In this paper we report for the first time that a major source of measurement noises comes from the periodical SDIO (Secure Digital Input Output) bus sleep inside the phone. The additional latency introduced by SDIO and Power Saving Mode can inflate and unstablize network delay measurement significantly. We carefully design and implement a scheme to wake up the phone for delay measurement by sending just enough warm-up and background traffic. Our evaluation results show that the overall median delay overheads can be kept within 3ms, regardless of the actual network delay.